PENGARUH KESELAMATAN KERJA, KESEHATAN KERJA DAN KOMITMEN ORGANISASI TERHADAPA KINERJA KARYAWAN PADA CV. YAMAHA WAJA MOTOR HAYAM WURUK DENPASAR - I Nyoman Rindra Hanjaswara; Ni Putu Lia Perdana Sari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
Performance isthe overall level ofsuccess of a person in a certain period where carrying out the task compared with various possibilities such as work standards, targets, targets or criteria which have been determined in advance and agreed upon together. This can be achieved if the company always pays attention to safety factors and occupational health because this will be able to improve employee performance. Occupational safety and occupational health is a program created by the government that must be obeyed and implemented by employers capable of workersin an effort to prevent accidents due to work and occupational diseases by recognizing things that have the potential to cause accidents and occupational diseases as well as anticipatory actionsin the event of an accident and occupational illness. On the other hand, organizational commitment is a sikao thatreflectssincewhere an individual knows and is bound to his organization. The aim of this study; 1) knowing the effect of work safety on employee performance, 2) knowing the effect of occupational health on employee performance, 3) knowing the effect of organizational commitment on employee performance, 4) knowing the effect of safety, occupational health and organizational commitment simultaneously on employee performance on CV Yamaha Waja Hayam Wuruk motorcycle. By using multiple linear regression analysis results are obtained; 1) occupational safety, occupational health, and organizational commitments positively influence employee performance on the Yamaha Waja Motor Hayam Wuruk CV. 2) work safety, occupational health, and organizational commitment simultaneously have a significant effect on employee performance on the Yamaha Waja Motor Hayam Wuruk CV. 3) work safety partially has a significant effect on employee performance at CV Yahamaha Waja Motor Hayam Wuruk. 4) the occupational health parsyal has a significant effect on employee performance on the Yamaha Waja Motor Hayam Wuruk CV. 5) partially organizational commitment has a significant effect on employee performance on theYamaha WajaMotorCVHayam Wuruk